2020
DOI: 10.11645/14.2.2680
|View full text |Cite
|
Sign up to set email alerts
|

Information literacy instruction in public libraries

Abstract: Extending from existing research on how public libraries offer information literacy (IL) instruction through classes or programs, the purpose of this research was to explore how public librarians provide IL instruction through individual interactions with patrons. US public librarians recorded their impressions of instructional interactions over a five-day period using an online diary instrument. Key findings were that public librarians incorporate a range of IL concepts in their interactions with patrons, acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Knjižnice imajo pomembno vlogo pri spodbujanju vrednot vseživljenjskega učenja, aktiv nega državljanstva in družbenega kapitala, ki zvišuje vključenost posameznika v družbo. S pomočjo izobraževanja o informacijski pismenosti lahko splošne knjižnice te vrednote promovirajo in razvijajo med svojimi člani (Matteson in Gersch, 2020).…”
Section: Izobraževanje In Informiranjeunclassified
“…Knjižnice imajo pomembno vlogo pri spodbujanju vrednot vseživljenjskega učenja, aktiv nega državljanstva in družbenega kapitala, ki zvišuje vključenost posameznika v družbo. S pomočjo izobraževanja o informacijski pismenosti lahko splošne knjižnice te vrednote promovirajo in razvijajo med svojimi člani (Matteson in Gersch, 2020).…”
Section: Izobraževanje In Informiranjeunclassified
“…Public libraries achieve IL in a less formal approach. For instance, Matteson and Gersch (2020) found that librarians provide situational guidance and support to their customers regarding their information needs. Moreover, public libraries offer ICT access and training, one-to-one reference interviews, and have partnerships with schools, volunteers, and various types of organisations (Crawford, 2014; Harding, 2008: 281–285; Lloyd, 2010: 125–127; McLean, 2008: 63–64; ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Information literacy plays an important role in facilitating sharing of information among library users through meetings, discussions, seminars, workshops, publications and so on. Hence in order to apply information into practice, public libraries should equip users with relevant skills in communicating information and knowledge (Matteson and Gersch, 2020).…”
mentioning
confidence: 99%